The effect of darkness duration on energy performance indicators in energy management system - Gürsu, Barış (Türkiye Enerji Stratejileri ve Politikaları Araştırma Merkezi (TESPAM), 2026)
[Abstract Not Available]
Keywords: Elektrik Mühendisliği; Enerji; Enerji Sistemleri Mühendisliği